A Checklist of Turkish Rotifers - Ustaoglu, Mustafa Rusen; Altindag, Ahmet; Kaya, Murat; Akbulut, Nuray; Bozkurt, Ahmet; Mis, Didem Ozdemir; Okgerman, Hacer Canan (Tubitak Scientific & Technological Research Council Turkey, 2012)
In a book chapter containing the first checklist and distribution of Turkish rotifers, published in 1999, were listed 167 taxa. The second checklist, published in 2004, reported 229 rotifer taxa in Turkey. During the 7 years since this checklist process, many studies have been carried out and we have prepared a new checklist of Turkish rotifers in the present study. In all, 341 rotifer taxa have been recorded to date.
Keywords: Checklist; Rotifera; inland waters; Turkey